A completely distributed transmission algorithm for mobile device-to-device caching networks. (October 2020) - Jeong, Moo-Woong; Ryu, Jong Yeol; Kim, Seong Hwan; Lee, Woongsup; Ban, Tae-Won
Abstract: We investigate mobile device-to-device (D2D) caching networks where mobiles called receiving devices (RDs) can receive data directly from caching server devices (CSDs). In mobile D2D caching networks, the quality of communications can be greatly enhanced because end-to-end communication ranges are shortened compared to cellular communications. In this paper, we propose a completely distributed transmission algorithm for mobile caching networks (DMC) based on signal-to-generating interference ratio (SGIR) that can eliminate overhead for signaling and feedback. In the DMC, each CSD autonomously chooses an RD to transmit data to and the CSD multicasts the data to RDs that requested the same data. One CSD is only activated to transmit data to each RD in a distributed manner based on timers. Our numerical results show that the DMC can yield comparable average sum-rates to a centralized scheme in various environments with no extra overhead. Graphical abstract: Highlights: We propose a distributed transmission algorithm for mobile caching networks. The proposed scheme can enhance the performance of mobile caching networks. The average sum-rates of the proposed scheme approach those of a centralized scheme.